2020
DOI: 10.1159/000508620
|View full text |Cite
|
Sign up to set email alerts
|

Home Range Size and Seasonal Variation in Habitat Use of Aye-Ayes (Daubentonia madagascariensis) in Torotorofotsy, Madagascar

Abstract: Madagascar’s dramatic climatic fluctuations mean most lemurs adjust behaviors seasonally as resource availability fluctuates. Many lemurs will adopt one of two strategies, a resource maximizer or an area minimizer, when adjusting to seasonal shifts in resource availability. However, it is unknown if and how aye-aye (<i>Daubentonia madagascariensis</i>) ranging behavior is influenced by seasonality. We explored whether habitat use changed seasonally. We followed two aye-ayes, an adult male and an ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 73 publications
1
10
0
Order By: Relevance
“…However, because these values were determined based solely on sleeping sites, they may not be directly comparable to our results which also included data on the female's ranging behavior. Additionally, recent findings from Torotorofotsy revealed that an adult female aye-aye had a home range of 765 ha and traveled at an average rate of 300 m/h [Sefczek et al, 2020a]. Although the distance traveled per hour by the female aye-aye at Torotorofotsy is remarkably similar to what we have found at Anjajavy, the home DOI: 10.1159/000520332 range of the female aye-aye at Torotorofotsy was much larger.…”
Section: The Ecology Of Aye-ayes Across Habitatssupporting
confidence: 74%
See 2 more Smart Citations
“…However, because these values were determined based solely on sleeping sites, they may not be directly comparable to our results which also included data on the female's ranging behavior. Additionally, recent findings from Torotorofotsy revealed that an adult female aye-aye had a home range of 765 ha and traveled at an average rate of 300 m/h [Sefczek et al, 2020a]. Although the distance traveled per hour by the female aye-aye at Torotorofotsy is remarkably similar to what we have found at Anjajavy, the home DOI: 10.1159/000520332 range of the female aye-aye at Torotorofotsy was much larger.…”
Section: The Ecology Of Aye-ayes Across Habitatssupporting
confidence: 74%
“…For example, like other aye-ayes, the reintroduced female spent the majority of her time feeding, moving/traveling and resting. Her home range of 85 ha is within the known limits for female aye-aye home ranges of 30-765 ha [Sterling and McCreless, 2006;Randimbiharinirina et al, 2018;Sefczek et al, 2020a]. She built, refurbished and reused nests in the upper canopy comprising fresh and dead foliage.…”
Section: Was Anjajavy's Aye-aye Reintroduction Successful?mentioning
confidence: 86%
See 1 more Smart Citation
“…At this time, it would be inappropriate to attribute this infanticidal event to a single hypothesis. There is at least one other male in this female's territory [Sefczek et al, 2020b], so there is likely male competition for reproductive opportunities, as well as intraspecific competition for resources. Yet, we lack additional information on subsequent siring by the infanticidal male or additional observed infanticidal events that would be necessary to contextualize the adaptive benefit of this behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In the reforestation areas, a majority of the camera trapping sites (N = 22) were located closer to one another (~0.35 km apart) due to the constricted amount of area from fragmentation and the need to have an appropriate number of trapping sites for occupancy modeling. Most lemur home ranges were unlikely to overlap multiple camera sites in fragments, except for the most wide-ranging species such as aye-ayes (Sefczek et al, 2020).…”
Section: Data Collectionmentioning
confidence: 99%